Geologic subjects: nonhuman origins, geomorphic aesthetics and the art of becoming inhuman - Yusoff, Kathryn (Cultural geographies, 2015)
This paper addresses the formation of subjectivity in the context of rock art, focusing on two prehistoric moments that exhibit the interrelation of nonhuman and inhuman forces in the art of becoming human. The first geologic subject of the prehistoric that is discussed is the ‘Birdman’ of Lascaux as an originary figure in human origins. The second subjects are the Gwion Gwion figures that were painted with the ‘living pigments’ of bacteria and fungi that continue to reproduce over geologic time to produce an image of human identity. This foray into the Palaeolithic imagination is done for two reasons: firstly, to examine the conceptual and corporeal genealogy of geologic subjectivity through an inquiry into originary and symbolic images; secondly, to examine geomorphic aesthetics as a space of inquiry within the apprehension of the Anthropocene. Methodologically, this paper moves beyond the boundary-work of hybridity to argue for the consideration of a queer ecology where subjects emerge as a constellation between inhuman time, nonhuman forces, and geologic materialities. In the opening of subject positions to nonhuman and inhuman forces, as both interior and prior to the emergence of identity, this paper argues that subjectivity always contains both an anterior and interior nonhuman excess; a surplus to identity that opens to non-normative arrangements that queries origins to suggest a queer genealogy, rather than an exceptional model of human subjectivity. In abandoning the assumption of discrete, identity-making autopoetic subjects, I explore the possibilities for apprehending a nonlocal, inhuman dimension of subjectivity that is difficult to accommodate in a relational ontology. Ecologies of subjectivities are discussed through the rock images to argue that the human is both constituted and riven by the torques of nonlocal forces in both identity and etiology, and this needs to constitute a new ontology of in/human sociality. I conclude that aesthetics possess an untimely quality that allows a passage into the radically incommensurate time of the geologic and therefore provide a possible site and mode of sensibility for engaging with the temporal and material contractions of the Anthropocene.